EFFECT OF REFRIGERATION PROCESSING ON THERAPEUTIC LACTIC ACID BACTERIA USED IN THERAPEUTIC YOGHURT PRODUCTION BY USING SOME STABILIZERS - H. Mohammed (Mesopotamia Journal of Agriculture)
This study included the implementation of refrigerating processing to preserve the probiotic yoghurt produced by using (ABT) starters through four weeks using five types of stabilizers (starch. CMC. gelatin. dextrin and inulin) which then compared with control sample (i.e. nostabilizer added).Yoghurt analysis was carried out at zero time and one week intervals. They were chemical: total acidity percentage pH curd drainage and microbiological: (total count. lactic acid bacteria (LAB) percentage of resistant LAB) and sensory evaluation: (flavour. consistency. appearance and acidity taste).Processing of 7% dextrin and 4% inulin surpassed in bacteria total count. Lab and percentage of resistant LAB. In addition. processing of 0.01% CMC was out standing in highest total acidity percentage. i.e. lowest pH. On the other hand processing of 7% dextrin gave the lowest amount of whey drainage. Concerning the sensory evaluations. the processing of 2.5% dextrin surpassed charactenistic and the processing of 7% dextrin surpassed in consistency charactenistic.However. for the appearance and acidity evaluation. the processing of 6% inulin was over whilmed.Throughout sensory charactenistics studied the processing of 4% inulin recorded the highest values (91.76%) in comperison with the control (81.56%).